Response to Comment on "Optimizing Post-Activation Performance Enhancement in Athletic Tasks: A Systematic Review with Meta-Analysis for Prescription Variables and Research Methods"...Xu K, Blazevich AJ, Boullosa D, et al. Optimizing Post-activation Performance Enhancement in Athletic Tasks: A Systematic Review with Meta-analysis for Prescription Variables and Research Methods. Sports Medicine (SPORTS MED), 2025; 55(4): 977-1008. - Xu, Kai; Blazevich, Anthony J.; Boullosa, Daniel; Ramirez-Campillo, Rodrigo; Yin, MingYue; Zhong, YuMing; Tian, YuHang; Finlay, Mitchell; Byrne, Paul J.; Cuenca-Fernández, Francisco; Wang, Ran (Sports Medicine, 2026)
This reply addresses a commentary on a recent meta-analysis concerning post-activation performance enhancement (PAPE). The authors acknowledge the importance of the placebo effect in influencing PAPE outcomes and support the inclusion of placebo-controlled conditions in future research designs. They highlight the value of assessing participants' expectations, referencing a methodological approach by Blazevich et al. as a useful model. Additionally, the authors suggest distinguishing PAPE effects from performance improvements due to mental imagery training, emphasizing the need for refined experimental designs to better quantify and apply PAPE in practice.